1989
DOI: 10.1210/jcem-68-1-135
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Response Characteristics for Suppression of Low Molecular Weight Plasma Insulin-Like Growth Factor-Binding Protein by Insulin*

Abstract: We previously demonstrated that supraphysiological insulin concentrations reduced the plasma 34K insulin-like growth factor-binding protein (IGF-BP) concentrations in humans. In this study we examined whether physiological changes in plasma insulin concentrations regulate IGF-BP and, if so, whether the regulation is influenced by race, glucose tolerance, or rate of glucose metabolism. For these purposes we 1) analyzed the relationship between fasting plasma insulin and IGF-BP concentrations in 2 racial groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
2
3

Year Published

1991
1991
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(77 citation statements)
references
References 27 publications
6
66
2
3
Order By: Relevance
“…There are several studies in which IGFBP-1 was shown to be a marker of hyperinsulinaemia [1,32,33]. As expected, fasting IGFBP-1 concentrations correlated inversely with fasting insulin levels in our study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…There are several studies in which IGFBP-1 was shown to be a marker of hyperinsulinaemia [1,32,33]. As expected, fasting IGFBP-1 concentrations correlated inversely with fasting insulin levels in our study.…”
Section: Discussionsupporting
confidence: 89%
“…IGFBP-1 synthesis is regulated by insulin and other factors that are altered in conditions associated with abnormal glucose regulation. The suppression of IGFBP-1 production by insulin is achieved within the physiological range of insulin concentrations [1][2][3]. There are multiple stimulators, including glucagon [4] and inflammatory cytokines [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The decrease in caruncle expression of IGFBP-1 can be attributed to two possible mechanisms. First, IGFBP-1 is inversely regulated by insulin (Suikkari et al 1989), and it has been shown previously that GH administration during gestation leads to hyperinsulinemia (Wallace et al 2004). Given that we achieved significant stimulation of IGF-I similar to that reported by Wallace et al one could reason that we generated a similar insulin response that reduced caruncle expression of IGFBP-1.…”
Section: Discussionsupporting
confidence: 76%
“…Thus, the turnover of IGF present in the ternary complex is relatively slow (7). In contrast to IGFBP-3, the levels of IGFBP-1 vary considerably throughout the day and are inversely regulated by insulin (5,11,21,22). The unique pattern of regulation of IGFBP-1 expression suggests that this binding protein may have some role in modulating the free component of IGF-I and thus may be important in blood glucose control (5).…”
Section: Discussionmentioning
confidence: 99%